Effect of Chemical Structure on the Electrochemical Cleavage of Alkoxyamines - Hammill, C.L.; Noble, B.B.; Norcott, P.L.; Ciampi, Simone; Coote, M.L. (AMER CHEMICAL SOC, 2019)
A test set of 14 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO)-based alkoxyamines was studied via a combination of cyclic voltammetry and accurate quantum chemistry to assess the effect of substituents on electrochemical cleavage. The experimental oxidation potentials of alkoxyamines falling into the range of 1.1-1.6 V versus Ag/AgCl in acetonitrile, were well reproduced by theory (MAD 0.04 V), with values showing good correlation with the σR Hammett parameters of both the R-group and the OR-group in TEMPO-R. Importantly, most of the studied alkoxyamines underwent oxidative cleavage to form either TEMPO· and R+ or TEMPO+ and R·, with the former favored by electron-donating substituents on R (e.g., 2-oxolane, Ac, CH(CH3)Ph, i-Pr, t-Bu) and the latter by electron withdrawing substituents (Bn, allyl, CH(CH3)C(O)OCH3, C(CH3)2C(O)OCH3, CH(CH3)CN). Where R is not stabilized (e.g., R = CH2C(O)OCH3, Me, Et), fully or almost fully reversible oxidation - without cleavage - was observed, making these species promising candidates for battery applications. Finally, in the case of R = Ph, where N-O cleavage occurred, a phenoxy cation and an aminyl radical were generated. On the basis of these results, TEMPO-based alkoxyamines can provide a variety of electrochemically generated carbon-centered radicals and carbocations for use in synthesis, polymerization, and surface modification.